Nanoceria-modified platinum supported on hierarchical zeolites for selective alcohol oxidation. Issue 62 (5th November 2019) - Ketkaew, Marisa; Suttipat, Duangkamon; Kidkhunthod, Pinit; Witoon, Thongthai; Wattanakit, Chularat
Abstract : Illustration of Pt/CeO2 supported on hierarchical zeolites promoting the highly selective oxidation of benzyl alcohol to benzaldehyde. Abstract : The highly selective oxidation of alcohols to aldehydes has been achieved due to the synergic effect of Pt and CeO2 supported on hierarchical zeolites. The combination of Pt and CeO2 strongly enhances the catalytic performance of the oxidation of benzyl alcohol to benzaldehyde with respect to the isolated materials. In addition, the hierarchical zeolite not only increases the fraction of exposed active sites because of its high surface area that can prevent the aggregation of Pt and CeO2 nanoparticles, but also affects the oxidation state of cerium. The presence of a high content of trivalent Ce species (Ce 3+ ) on the hierarchical zeolite benefits the oxidation reaction, eventually leading to almost 100% yield of an aldehyde product. Moreover, the catalytic performance can be further improved by the easily tunable Si to Al ratio of zeolite catalysts.